2014
DOI: 10.1039/c4nr00733f
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic/organic hybrid solar cells: optimal carrier transport in vertically aligned silicon nanowire arrays

Abstract: Inorganic/organic hybrid radial heterojunction solar cells that combine vertically-aligned n-type silicon nanowires (SiNWs) with poly(3,4-ethylenedioxythiophene):poly(styrene-sulfonate) (PEDOT:PSS) have great potential for replacing commercial Si solar cells. The chief advantage of such solar cells is that they exhibit higher absorbance for a given thickness than commercial Si solar cells, due to incident light-trapping within the NW arrays, thus enabling lower-cost solar cell production. We report herein on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…For the Si substrate with such micro-textured surfaces, the PEDOT:PSS layer, which is a p-type-like conjugated conducting polymer, was spin-coated at a spin speed of 7500 rpm. We have previously confirmed that for micro-pyramidal structures [11] and nanowire array structures [19] this spin speed enables the PEDOT:PSS layer to better adhere on micro-textured surfaces. The morphology of the PEDOT:PSS layer on the micro-desert textured surfaces and honeycomb surfaces was analyzed by means of cross-sectional SEM micrographs, as shown in Figures 2a and 2b, respectively.…”
Section: Morphology and Antireflection Effect Of Si/pedot:pss Composimentioning
confidence: 63%
See 4 more Smart Citations
“…For the Si substrate with such micro-textured surfaces, the PEDOT:PSS layer, which is a p-type-like conjugated conducting polymer, was spin-coated at a spin speed of 7500 rpm. We have previously confirmed that for micro-pyramidal structures [11] and nanowire array structures [19] this spin speed enables the PEDOT:PSS layer to better adhere on micro-textured surfaces. The morphology of the PEDOT:PSS layer on the micro-desert textured surfaces and honeycomb surfaces was analyzed by means of cross-sectional SEM micrographs, as shown in Figures 2a and 2b, respectively.…”
Section: Morphology and Antireflection Effect Of Si/pedot:pss Composimentioning
confidence: 63%
“…Thus, the micro-desert textured hybrid solar cell showed a low J sc value owing to the reduced collection rate of the separated electrons at the rear electrode by the occurrence of carrier recombination. In contrast to the J sc value, the high V oc value was related to the high shunt resistance (R sh ), which caused low power losses in the hybrid solar cells [19] , whereas the high FF arose from the low series resistance (R s ). The micro-desert textured hybrid solar cell had a high R sh value of 5.41 × 10 1 Ωcm 2 , and a low R s value of 1.15 Ωcm 2 in comparison with the honeycomb structured cell because of the complete adhesion of the PEDOT:PSS layer throughout the micro-desert textures.…”
Section: Effect Of the Texture Of The Antireflection Layer In Si/pe-dmentioning
confidence: 85%
See 3 more Smart Citations